Las novelas de un biógrafo (Benjamín Jarnés). - Pego Puigbó, Armando (Dicenda. Estudios de lengua y literatura españolas, 1999)
Ihis paper deals with two novels writíen by Benjamín Jarnés: El convidado depapel (1928) and Lo rojo y lo azul (1932). Through an analysis of the two novels, the Iimits of Spanish vanguard novel in the fleld of biography, autobiography ané fiction are discussed. An understanding of Ihe characters is based on te relationship between Iheory, ciitics and philosophy. An interpretation of metaphor shows that the characíers mi«or Jarnés’ desires lot identity. Consequently, the narrative becomes a metafictional process that reveals his life through art.